Intergenerational transmission and economic self-sufficiency - Tosun, Jale; Pauknerová, Daniela; Kittel, Bernhard (Springer International Publishing, 2021)
1. Intergenerational transmission of economic self-sufficiency: an introduction; Jale Tosun, Daniela Pauknerová and Bernhard Kittel -- 2. Analytical Framework; Jale Tosun, Daniela Pauknerová and Bernhard Kittel -- 3. Ambitions and Traditions: Intergenerational Transmission of Work Attitudes in Austria; Julia-Rita Warmuth, Stefanie Stadlober, Eva Wimmer & Bernhard Kittel -- 4. Looking Beyond the Family Nest: Self-sufficiency of Young Adults and Intergenerational Transmission of Values and Resources in Czech Republic; Daniela Pauknerová, Zuzana Chytkova and Jan Hanzlík -- 5. Limits of Welfare. How the family remains pivotal for work attitudes in the “youth enabling” welfare state of Denmark; Christoph Arndt and Carsten Jensen -- 6. Between adaption and rejection: Intergenerational transmission of resources and work values in Germany; Robert Strohmeyer and Julia Weiß -- 7. Intergenerational Transmission of Resources and Values in Times of Crisis: Shifts in Young Adults’ Employment and Education in Greece ; Asimina Christoforou, Evmorfia Makantasi, Kyriakos Pierrakakis & Panos Tsakloglou -- 8. By the Sweat of Your Parents’ Brow: Self-sufficiency of Young Adults and Intergenerational Transmission of Values and Resources in Hungary Dániel Kovarek and Róbert Sata -- 9. Family history matters: the road to self-sufficiency in Italy; Maurizio Caserta, Livio Ferrante, Simona Monteleone, Francesco Reito, Salvatore Spagano -- 10. Intergenerational Transmission of Family Work Values and Economic Self-Sufficiency of Young Individuals in Spain; José L. Arco-Tirado, Francisco Fernández-Martín, Irene Herranz and Mihaela Vancea -- 11. Dependently Independent: Intergenerational Transmission of Values, Attitudes, and Resources in Switzerland; Carolin Rapp and Kerstin Nebel -- 12. Differences Across Generations and Stability of Values in the Turbulence of Social Change; Nebi Sümer, Zeynep Cemalcılar, Haluk Mert Bal -- 13. Cash and Class: Intergenerational transmission of values and capital and the consequences for social mobility in the UK; Emily Rainsford and Anna Wambach -- 14. Conclusion; Jale Tosun, Daniela Pauknerová and Bernhard Kittel.